Faktor-Faktor Keunggulan dan Keberhasilan Koperasi: Perspektif Pendidikan Manajemen Ekonomi - Rusmiati Rusmiati; Rindiani Rindiani; Dewi Mitasari; Chika Dewi Santika (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This article examines various factors that determine the success and competitiveness of cooperatives in Indonesia from the perspective of economic management education. The analysis draws upon recent empirical studies, theoretical reviews, and case-based comparisons published in the past five years. Findings reveal that institutional governance, member participation, digital innovation, cooperative education, and capital structure are key determinants of cooperative performance. Educational efforts in management, especially in vocational and community-based settings, significantly influence the sustainability and competitiveness of cooperatives in the modern economy.